2016
DOI: 10.1371/journal.pone.0153900
|View full text |Cite
|
Sign up to set email alerts
|

Where Is My Food? Brazilian Flower Fly Steals Prey from Carnivorous Sundews in a Newly Discovered Plant-Animal Interaction

Abstract: A new interaction between insects and carnivorous plants is reported from Brazil. Larvae of the predatory flower fly Toxomerus basalis (Diptera: Syrphidae: Syrphinae) have been found scavenging on the sticky leaves of several carnivorous sundew species (Drosera, Droseraceae) in Minas Gerais and São Paulo states, SE Brazil. This syrphid apparently spends its whole larval stage feeding on prey trapped by Drosera leaves. The nature of this plant-animal relationship is discussed, as well as the Drosera species inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 68 publications
4
20
1
1
Order By: Relevance
“…Estudios como el aquí presentado pueden ayudar a un mejor conocimiento de la distribución local, regional y mundial de las especies de Syrphidae y al descubrimiento de nuevos y llamativos ciclos biológicos (Fleischmann et al 2016), que pueden ser de gran ayuda en el manejo de ecosistemas, control biológico de plagas o en los servicios de polinización en agrosistemas e invernaderos.…”
Section: Resultados Y Discusiónunclassified
“…Estudios como el aquí presentado pueden ayudar a un mejor conocimiento de la distribución local, regional y mundial de las especies de Syrphidae y al descubrimiento de nuevos y llamativos ciclos biológicos (Fleischmann et al 2016), que pueden ser de gran ayuda en el manejo de ecosistemas, control biológico de plagas o en los servicios de polinización en agrosistemas e invernaderos.…”
Section: Resultados Y Discusiónunclassified
“…Such a hypothesis is contingent upon the assumption that predatory pitcher inquilines return a significant fraction of consumed nitrogen to pitchers through nitrogenous wastes. Such an assumption remains unproven, as neither Scharmann et al [6] nor Chua & Lim [7] demonstrated this in their studies on C. schmitzi and M. nepenthicola, respectively, while Fleischmann et al [8] argued that some inquilines never return this nitrogen to their carnivorous plant hosts. Clarke & Kitching [9] speculated that C. schmitzi excreta returned a fraction of consumed nitrogen to their N. bicalcarata hosts, but their results showed that C. schmitzi presence in pitchers resulted in net reductions in fluid ammonium concentrations.…”
Section: Introductionmentioning
confidence: 96%
“…Commonly known as flower flies or hoverflies, syrphids (Diptera: Syrphidae) are distributed worldwide, absent only in remote oceanic islands and Antarctica (Thompson & Rotheray, 1998). While adults feed on pollen and nectar, larvae have a large array of natural histories (Ureña & Hanson, 2010;Rotheray & Gilbert, 2011;Pérez-Lachaud et al, 2014;Fleischmann et al, 2016). Syrphid species have been used as bioindicators (Sommaggio, 1999;Tscharntke et al, 2005;Ricarte et al, 2011;Sommaggio & Burgio, 2014), and they contribute to very important ecosystem services, such as pollination, biological control of pests or decomposition of organic matter (Lardé, 1989;Schmidt et al, 2004;Bergh & Short, 2008;Bugg et al, 2008;Ssymank & Kearns, 2009;Morales & Wolff, 2010;Martínez-Falcón et al, 2012;Nelson et al, 2012;Inouye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%